Viva Voce of Biochemistry. - Rao, B. Prabhakar (New Age International Pvt. Ltd., Publishers, 2007)
The idea of writing this book of VIVA VOCE/ORALS IN BIOCHEMISTRY is that, it should be much helpful to the MBBS and M. Sc. (Medical Science) students and postgraduate students for the preparation of examination. Though it is not a textbook of Medical Biochemistry, it is framed in the form of questions and answers in a simplified way. The book will definitely help the students for the preparation of their examinations.